Coronal and Transverse Malalignment in Pediatric Patellofemoral Instability - Robert C. Palmer (Journal of Clinical Medicine, 2021)
Patellofemoral instability (PFI) encompasses symptomatic patellar instability, patella subluxations, and frank dislocations. Previous studies have estimated the incidence of acute patellar dislocation at 43 per 100,000 children younger than age 16 years. The medial patellofemoral ligament (MPFL) complex is a static soft tissue constraint that stabilizes the patellofemoral joint serving as a checkrein to prevent lateral displacement. The causes of PFI are multifactorial and not attributed solely to anatomic features within the knee joint proper. Specific anatomic features to consider include patella alta, increased tibial tubercle–trochlear groove distance, genu valgum, external tibial torsion, femoral anteversion, and ligamentous laxity. The purpose of this paper is to provide a review of the evaluation of PFI in the pediatric and adolescent patient with a specific focus on the contributions of coronal and transverse plane deformities. Moreover, a framework will be provided for the incorporation of bony procedures to address these issues.